Activated Carbon from Mulu Bebe Stem Waste for Methylene Blue (MB) Adsorption - Indra Cipta; Nur Jannah Baturante; Zulkifli Zam Zam; Angela Pasimanyeku; Yunita Pare Rombe (TECHNO: JURNAL PENELITIAN, 2024)
Methylene blue is a harmful synthetic dye waste component that poses a significant threat to the environment and human health if not disposed of properly. The best way to tackle this problem is by adsorption through activated carbon from Mulu Bebe banana stems, which are widely available in North Maluku. This agricultural waste can be used to produce activated carbon through pyrolysis at 500ËšC for 30 minutes and activation using 0.5 M KOH solution for 24 hours. The activated carbon is then characterized using FTIR, SEM and XRD, which reveal the presence of various functional groups and pores. The XRD results indicate that the activated carbon structure tends to be amorphous. The adsorption analysis shows that the activated carbon from Mulu Bebe banana stems has a high adsorption capacity of 12.4 mg/g at the optimum condition of pH 7, contact time of 30 minutes, and initial concentration of 50 ppm. The Langmuir and Freundlich equations provide the best fit for the equilibrium adsorption data. By using activated carbon from Mulu Bebe banana stems, we can effectively reduce the amount of methylene blue waste in the environment and protect the ecosystem and human health.